Firenze, biblioteca mediceo-laurenziana, pluteo 29, I - Dittmer, Luther A. (Brooklyn, NY Institute of Mediaeval Music, 1967)
Pluteo 29.1, also known as Pluteus 29.1, or simply the Florence Manuscript, is an illuminated manuscript in the Laurentian Library of Florence.The manuscript is believed to have been produced by the workshop of Johannes Grusch in Paris during the mid-thirteenth century, probably between 1245 and 1255. It contains the largest extant collection of music in the Notre-Dame style, mainly organa, conductus, and motets. The illumination consists of thirteen historiated initials and one full-page miniature which serves as its frontispiece.The manuscript was issued in facsimile by Institute of Medieval Music in 1967